Bentuk Pertunjukan Tari Mancak Padang Dalam Upacara Urak Balabek Di Nagari Pauh IX Kota Padang - Vivi Andriani; Nerosti Nerosti (FBS Universitas Negeri Padang, 2021)
This study aims to describe the form of Mancak Padang Dance Performance in Urak Balabek Ceremony at Pauh IX Village, Kuranji District, Padang City.This research belongs to a qualitative research using analytical descriptive method. The object of research was Mancak Padang Dance in Pauh IX Village, Kuranji District, West Sumatra Province. It is focused on the form of performance. The data were collected through literature review, observation, interview, and documentation. The data analysis was conducted by using triangulation technique which compared the observation result data with the data from interview and documentation. The results of the study generally show that Mancak Padang Dance in Urak Balabek ceremony in Pauh IX Village, Kuranji District, is a village party in the context of adopting sasian to become aguru tuo and give the title. Urak Balabek ceremony is a procession of crowning someone to lift his sword. This ceremony must be attended by boys. It is to indicate that the boy is mature enough to carry on the inheritance from the previous to the present generation. This activity begins by slaughtering a buffalo. The role of women is also needed to prepare for the banquet. The first night is the government ceremonial opening andalek ceremony.Next, galanggang opening which is opened by the head of pandeka with mancak padang. It is continued by Mancak Padang dance by the kids. After that, the guru tuo perform Mancak Padang dance, and it is closedby guru gadang. Mancak Padang dance movement originates from silat divided into three: kuda-kuda, balabekandgelek. Mancak Padang dance is accompanied by external music in the form of drums.Costumes wornare black silatclothes and a sarungin the waist. Mancak Padang dance in Urak Balabek Ceremony must be preserved from generation to generation. This is due to the fact thatthe dance is one of the traditional and cultural traditions as well as local wisdom owned by the community of Pauh IX Village, Kuranji District, West Sumatra Province.